Analisis Proses Pendampingan UMKM Nasabah BTPN dalam Penguatan Brand Identity di Wiyung - Prijatna, Ayesha Naima Zahra; Mandasari, Virginia (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute over 60% to Indonesia’s GDP, yet most MSME actors face challenges in building strong brand identity due to limited branding knowledge and digital literacy. This research analyzes the business mentoring process in strengthening brand identity of BTPN MSME customers in Wiyung, Surabaya. A qualitative descriptive method was employed using participatory observation, in-depth interviews with five MSME actors. Findings reveal that participatory mentoring successfully enhanced MSME actors’ understanding of brand identity, produced tangible changes in visual elements such as logos and packaging design, and increased entrepreneurial confidence and motivation. MSME actors also demonstrated improved utilization of digital platforms for promotion. The mentoring effectively strengthened all six dimensions of Kapferer’s brand identity model. This research confirms that business mentoring plays a strategic role in building MSME independence and strengthening their market competitiveness.